2016
DOI: 10.1186/s13287-015-0266-z
|View full text |Cite
|
Sign up to set email alerts
|

CD146/MCAM defines functionality of human bone marrow stromal stem cell populations

Abstract: Background: Identification of surface markers for prospective isolation of functionally homogenous populations of human skeletal (stromal, mesenchymal) stem cells (hMSCs) is highly relevant for cell therapy protocols. Thus, we examined the possible use of CD146 to subtype a heterogeneous hMSC population. Methods: Using flow cytometry and cell sorting, we isolated two distinct hMSC-CD146 + and hMSC-CD146 − cell populations from the telomerized human bone marrow-derived stromal cell line (hMSC-TERT). Cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 41 publications
2
76
1
Order By: Relevance
“…Similar to our in vitro results, Harkness et al reported that bone formation was significantly enhanced in subcutaneous implants containing CD146 - cells, indicating a higher osteogenic potential of this fraction [22]. They also detected a higher plasticity and the ability of transendothelial migration of CD146 + cells, which suggests that CD146 + cells are recruited to the bone surfaces by chemotactic attraction, and the subsequent maturation to osteoblasts goes hand in hand with the loss of CD146 expression.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to our in vitro results, Harkness et al reported that bone formation was significantly enhanced in subcutaneous implants containing CD146 - cells, indicating a higher osteogenic potential of this fraction [22]. They also detected a higher plasticity and the ability of transendothelial migration of CD146 + cells, which suggests that CD146 + cells are recruited to the bone surfaces by chemotactic attraction, and the subsequent maturation to osteoblasts goes hand in hand with the loss of CD146 expression.…”
Section: Discussionsupporting
confidence: 78%
“…The low efficiency of magnetic CD146 separation was also described in the current work of Harkness and co-authors [22]. They also obtained significantly higher efficiencies of CD146 enrichment from a mesenchymal stem cell line overexpressing a human telomerase, using FACS in comparison to MACS separation.…”
Section: Discussionmentioning
confidence: 71%
“…We focused our study on CD31 − DP-MSCs to exclude cells that may express some of these markers although being not MSCs. Indeed, some endothelial cells are known to express CD146 and Stro-1, and natural killer cells and some lymphocytes may express CD56 (Shi and Gronthos, 2003; Woodfin et al, 2007; Crisan et al, 2008; Ge et al, 2013; Lv et al, 2014; Harkness et al, 2016; Melsen et al, 2016). Flow cytometry was recently used to characterize the various populations of immune cells present in the human DP with a strategy of progressive cell gating (Gaudin et al, 2015), and we designed in the present study a similar strategy to allow for the identification and quantification of DP-MSC subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Although no definitive MSC markers have been identified so far (Lv et al, 2014), DP-MSC populations have been characterized mainly on the basis of the expression of cell surface molecules including the bone marrow cell membrane antigen Stro-1 (Gronthos et al, 2000; Alliot-Licht et al, 2005), the melanoma cell adhesion molecule MCAM/CD146 (a marker of perivascular MSCs; Shi and Gronthos, 2003; Lv et al, 2014; Harkness et al, 2016), the low affinity nerve growth factor receptor p75NTR/CD271 (Waddington et al, 2009; Lv et al, 2014; Alvarez et al, 2015; Tomlinson et al, 2016), the mesenchymal stem cell antigen MSCA-1 (also known as TNAP/Tissue Non-Specific Alkaline Phosphatase; Sobiesiak et al, 2010; Tomlinson et al, 2015), and the neural cell adhesion molecule NCAM/CD56 (a marker of neural and muscular MSC populations; Battula et al, 2009; Sobiesiak et al, 2010; Bonnamain et al, 2013; Lv et al, 2014). We recently isolated and easily amplified in culture a population of MSCs from the DP of human developing third molars with a medicinal manufacturing approach (Ducret et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In both human renal and prostate cancer cells, CD44 has been identified as a direct target of miR-34a [89], a miRNA that promotes osteogenesis in human adipose-derived stem cells [90]. In addition, the 3’UTR of CD146 , which has been associated with a higher potential for osteogenic differentiation [91], is directly targeted by miR-329 in endothelial cells [92]. Also in endothelial cells, expression of Vcam1 , which encodes the cell-cell adhesion molecule CD106 and reduces the migratory ability of MSCs [93], is controlled by miR-126 [94].…”
Section: Micrornas Associated With the Mesenchymal State And Mesenchymentioning
confidence: 99%